Naming the silences : God, medicine, and the problem of suffering - Hauerwas, Stanley, 1940- (Grand Rapids, MI : Wm. B. Eerdmans, 1990)
Drawing heavily on stories of ill and dying children to illustrate and clarify his discussion of theological issues, Stanley Hauerwas explores why we seek explanations for suffering and evil so desperately in today's world. Modern medicine, he declares, has too often become a noisy way to hide the gaping silences created by the painful experience of childhood illness and death. Alternatively, he shows us a God who "can give a voice to that pain in a manner that at least gives us a way to go on." --From publisher's description.
A Child's Dying -- Theology, Theodicy, and Medicine -- Medicine as Theodicy.
Includes bibliographical references (p. 152) and index.
Keywords: Suffering -- Religious aspects -- Christianity; Children -- Death -- Religious aspects -- Christianity; Theodicy; Medicine -- Religious aspects -- Christianity; Christianity -- 20th century; Consolation; Christian ethics -- Methodist authors